Repurposing Of Orphan Drug Transtuzumab For The Treatment Of Her2 Positive Gastric Cancer In U.S And India (International Journal of Research in Pharmacology & Pharmacotherapeutics, 2025)
There is a great need and opportunity for the development of medicines for rare orphan illnesses. In an increasing number of nations, it is projected that gastric cancer will become a rare disease. In recent years, the incidence of stomach cancer has continued to raise worldwide, accounting for 40% of all cases. The reality is that developing drugs for cancer is challenging, costly, and time-consuming, with only poor success rates. Due to the ineffectiveness of currently available treatments, their high cost, and the potential for therapy to lower quality of life, repurposing has become a crucial strategy in the development of anti-cancer medications. Repurposing that supports the alternate applications of existing medications is encouraged by regulatory bodies like the FDA. Trastuzumab is a repurposed orphan drug for the treatment of HER2 positive gastric cancer. Trastuzumab was added to standard chemotherapy in the ToGA study, which increased patient survival for those with HER2-positive advanced G/GEJ adenocarcinoma and moved these patients into a new era of HER2-targeted therapy. The importance of medication repurposing, as well as the regulatory procedure for repurposed drugs in the United States and India are summarized in this study